The Relationship between Self Efficacy, Effort, Auditor Time Budget Pressure and Audit Judgment Performance in Auditors in Indonesia - Muhsin, Muhsin (Green Publisher Indonesia, 2023)
This study aims to examine the relationship between research variables, namely self-efficacy, effort, auditor time budget pressure and audit judgment performance owned by Indonesian auditors. The sample in this study is auditors level I to level VII at BPK Republik Indonesia. Data were obtained by survey methods and purposive sampling techniques. The data collected in this study amounted to 90 respondents then tested using the SEM analysis technique of the Warp PLS 4.0 program. The results showed that self-efficacy has a positive and significant effect on effort, self-efficacy has a positive and significant effect on audit judgment performance, effort has a positive and significant effect on audit judgment performance, and auditor time budget pressure positively and significantly affects the relationship between effort and audit judgment performance.